Antisense globin RNA in mouse erythroid tissues: structure, origin, and possible function. - Volloch, V (1996)
The aim of the experiments described in this paper was to test for the presence of antisense globin RNA in mouse erythroid tissues and, if found, to characterize these molecules. The present study made use of a multistep procedure in which a molecular tag is attached to cellular RNA by ligation with a defined ribooligonucleotide. The act of ligation preserves the termini of RNA molecules, which become the junctions between cellular RNAs and the ligated ribooligonucleotide. It also unambiguously preserves the identity of cellular RNA as a sense or antisense molecule through all subsequent manipulations. Using this approach, we identified and characterized antisense beta-globin RNA in erythroid spleen cells and reticulocytes from anemic mice. We show in this paper that the antisense globin RNA is fully complementary to spliced globin mRNA, indicative of the template/transcript relationship. It terminates at the 5' end with a uridylate stretch, reflecting the presence of poly(A) at the 3' end of the sense globin mRNA. With respect to the structure of their 3' termini, antisense globin RNA can be divided into three categories: full-size molecules corresponding precisely to globin mRNA, truncated molecules lacking predominantly 14 3'-terminal nucleotides, and extended antisense RNA containing 17 additional 3'-terminal nucleotides. The full-size antisense globin RNA contains two 14-nt-long complementary sequences within its 3'-terminal segment corresponding to the 5'-untranslated region of globin mRNA. This, together with the nature of the predominant truncation, suggests a mechanism by which antisense RNA might give rise to new sense-strand globin mRNA.